Intermediate accounting - Nikolai, Loren A.; Bazley, John D.; Jones, Jefferson P. (South-Western Cengage Learning, 2010)
INTERMEDIATE ACCOUNTING, Eleventh Edition, provides the perfect combination of professional language and vibrant pedagogy to facilitate the transition from financial principles to the larger environment of financial reporting. To prepare students for professional accounting careers, the text's comprehensive coverage of GAAP and discussion of IFRS is clearly and consistently presented throughout the text. This coverage complements the authors' insight, which is in both the in-text commentary and the fully coordinated, author-written end-of-chapter material